Wearable Cardioverter Defibrillator–Guided 6-Min Walk Test Performed at Home Is Accurate and Reliable: RESULTS OF THE TRENDS STUDY. Issue 2 (March 2020) - Burch, Ashley E.; Scherr, Daniel; Rieth, Andreas; Griffin, John; Bianco, Nicole R.; Odeneg, Tanja; Sears, Samuel F.
Abstract : Purpose: The 6-min walk test (6MWT) is broadly used to evaluate the functional ability of patients with heart failure (HF). The purpose of this study was to evaluate the accuracy and reliability of the wearable cardioverter defibrillator (WCD)–guided 6MWT performed at home by patients with HF versus in-clinic testing. Methods: Patients (n = 197) with HF and a low ejection fraction prescribed a WCD were randomized to 2 groups. Group 1 completed an in-clinic clinician-guided 6MWT while wearing the WCD; results were recorded by the clinician. Group 2 completed a WCD-guided 6MWT, also performed in the clinic; results were recorded by the WCD accelerometer. Both groups performed weekly unsupervised WCD-guided 6MWTs at home, with results recorded by the WCD. Results: The initial in-clinic 6MWT showed no significant group difference in distance walked (group 1 = 306 m; group 2 = 297 m). For patients in group 2 who completed at least one 6MWT at home, there was a 15-step decrease between the in-clinic WCD-guided 6MWT and the first at-home 6MWT, 558 and 543 median steps ( P = .001), respectively. Among patients with at least 8 weekly home WCD-guided 6MWTs (n = 70), there was no significant difference in the number of steps walked during the 6MWT from week to week. Conclusions: Results of the in-clinic 6MWT are similar between clinician-guided and WCD-guided patients across objective distances. Distances walked with a WCD-guided walk test were consistent whether conducted in the clinic or at home and were reliable over time. Abstract : Supplemental Digital Content is Available in the Text.This study examined the accuracy and reliability of the wearable cardioverter defibrillator (WCD)–guided 6-min walk test (6MWT) performed at home by patients with heart failure versus in-clinic testing. Distances walked with a WCD-guided 6MWT were consistent whether conducted in the clinic or at home and were reliable over time.